1997
DOI: 10.1093/ije/26.suppl_1.s181
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of reproducibility and relative validity of the questions included in the EPIC Physical Activity Questionnaire

Abstract: The questions selected for the short questionnaire are not suitable for estimating energy expenditure at an absolute level. Reproducibility and relative validity of the ranking of subjects seemed satisfactory and comparable to the extensive questionnaire. The results imply that the short questionnaire is suitable for ranking subjects in the EPIC study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
235
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(237 citation statements)
references
References 14 publications
1
235
0
1
Order By: Relevance
“…40 In accordance with this, validation of the lifestyle questionnaire used in the present study showed that sport and cycling were closely associated with energy expenditure, whereas the 4 other low-intensity activities were weakly associated with energy expenditure. 30 Although the physical activity questions have performed well in validation, 31 some misclassification may still be present. Physical activity was assessed only at baseline and the reported physical activity may not reflect physical activity earlier in life nor changes after baseline, and furthermore, any protective effect of physical activity may require lifelong exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In accordance with this, validation of the lifestyle questionnaire used in the present study showed that sport and cycling were closely associated with energy expenditure, whereas the 4 other low-intensity activities were weakly associated with energy expenditure. 30 Although the physical activity questions have performed well in validation, 31 some misclassification may still be present. Physical activity was assessed only at baseline and the reported physical activity may not reflect physical activity earlier in life nor changes after baseline, and furthermore, any protective effect of physical activity may require lifelong exposure.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The performance of the physical activity questions was assessed among 126 men and women using an extensive physical activity questionnaire administered 3 times (at baseline and after 5 and 11 months) and the questionnaire was found to rank participants satisfactorily with regard to their physical activity level. 31 Data on physical activity included questions about the number of hours spent in a typical week, during summer and winter, in the past year, on 4 types of leisure time physical activities: sport (fitness, aerobics, swimming, jogging, tennis, etc. ), cycling (cycling to work, shopping and leisure time), walking (walking to work, shopping and leisure time) and gardening.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Blood pressure, weight, and height were measured by trained staff according to standardized protocols (Beulens et al 2010). Physical activity was assessed using a validated questionnaire (Haftenberger et al 2002) and classified according to the Cambridge Physical Activity Index (CPAI) with single imputed data for missing values (n = 4930) (Pols et al 1997). The CPAI has four categories, i.e., inactive, moderately inactive, moderately active, and active.…”
Section: Lifestyle and Anthropometric Variablesmentioning
confidence: 99%
“…Physical activity was measured with the questionnaire used in the EPIC-Spain cohort (15), and sedentary behavior was estimated by time spent watching television as assessed by the Nurse´s Health Study questionnaire validated in Spain (16). Food consumption in the previous year was collected using a validated computerized diet history developed from that used in the EPIC-Spain cohort study, and energy intake was calculated using Spanish food composition tables (17).…”
Section: Sociodemographic Variables Lifestyle Obesity and Reported mentioning
confidence: 99%